Influence of 1-butyl-3-methylimidazolium chloride ([BMIM] Cl) reaction temperatures to the toxicity and biodegradation of kapok cellulose film / Wahida Abdul Rahman, Siti Aishatun Abdul Wahab and Salamiah Zakaria - Abdul Rahman, Wahida; Abdul Wahab, Siti Aishatun; Zakaria, Salamiah (Universiti Teknologi MARA, Perlis, 2015)
The influence of the 1-butyl-3-methylimidazolium chloride ([BMIM] Cl) reaction temperature to the toxicity and biodegradation of kapok cellulose film were studied. In this study, ([BMIM] Cl) acted as a solvent to dissolve kapok cellulose by partial ionic dissolution method. The kapok cellulose films were produced by dissolving cellulose at various reaction temperature ranged from 60 oC to 100 oC. The toxicity of ([BMIM] Cl) has been related directly with the length of the butyl chain in the solvent. According to the Fourier Transform Infrared Spectroscopy (FTIR), the intensity of the peak which represented butyl chain (2800 – 3000 cm-1) decreased as the reaction temperature increased. This might be due to the butyl chain that has been vaporized at high temperature. Based on the biodegradation results, kapok cellulose film E degraded at fastest rate among other films. This film exhibited 93.56 % weight loss while the lowest was film A with 91.63 %. These results were in agreement with the previous study that stated the rate of degradation is enhanced as the reaction temperature increased. For moisture uptake test, moisture uptake continuously increased with the increasing time from day 1 to day 7 for all reaction temperatures. The percentage of moisture uptake drop subsequently after day 5 due to the moisture water uptake has reached the equilibrium in all samples.